Effect of Management Control System (MCS), Activity Based Management (ABM), and Value Chain on Effectiveness, Efficiency, Economic Value Added (EVA) and Its Impact on Profitability in Construction Service Companies in East Java Province - Hartantyo, Sugeng Dwi (Archives of Business Research, 2019)
purpose of the study was to analyze the effect of Management Control System (MCS), Activity Based Management (ABM), and Value Chain on Effectiveness, Efficiency, Economic Value Added (EVA) and Its Impact Against Profitability in Construction Service Companies in East Java Province. The type of research used in this study is quantitative research. Quantitative research is a method used to test certain theories by examining the relationship of how much influence between variables is the level of business competition and Islamic business ethics on the behavior of Muslim entrepreneurs with statistical analysis. This research is a survey research because it uses a data collection tool in the form of a questionnaire / questionnaire. The results of the questionnaire were then tested using validity test, reliability test. The population in this study were construction service companies incorporated in the Association of Indonesian National Construction Implementation Association (GAPENSI) East Java Province with K1 sub-qualifications of 978 companies, K2 as many as 1369 companies and K3 as many as 1194 companies with a total of 3541 construction service companies (contractors). The sample used in this study was 97 contractors. For this study data analysis used theapproach Partial Least Square (PLS). The results of this study indicate that; variable Management Control System (MCS) significantly affects the effectiveness variables, (2) variable Management Control System (MCS) significantly affects the variable efficiency, (3) the variable Management Control System (MCS) significantly affects the variable Economic Value Added(EVA),(4) Management Control System (MCS) variable has a significant effect on profitability variable (5) Activity Based Management (ABM) variable has a significant effect on effectiveness variable (6) Activity Based Management (ABM) variable influences efficiency variable (7)variable Activity BasedManagement (ABM) has a significant effect on the variables Economic Value Added (EVA), (8) Activity Based Management (ABM) variables have a significant effect on profitability variables, (9)variables Value Chain have no significant effect on effectiveness variables, (10)variables Value Chain significant effect on the efficiency variable (11) variable Value Chain experienc the effect is not significant on the variables Economic Value Added (EVA), (12)variables Value Chain have a significant effect on profitability variables, (13) effectiveness variables have a significant effect on profitability variables, (14) efficiency variables have a significant effect on profitability variables, (15) variables Economic Value Added (EVA) has a significant effect on profitability variables.